PENGARUH FLUKTUASI HARGA TERHADAP DAYA BELI PEDAGANG SEMBAKO MUSLIM DI PASAR PALAKKA KAB. BONE - Husna Hayati; Muh Arafah (Jurnal Akuntansi dan Keuangan Syariah (Jurnal Akunsyah), 2023)
This research discusses the effect of price fluctuations on purchasing power, or the purchasing power of traders, this study aims to determine whether fluctuations can affect the purchasing power of traders, the population in this study was 100 people and samples were taken based on the slovin formula as many as 80 respondents, this research was an ex post facto research the type of research used was quantitative using data collection techniques in the form of questionnaires, while the data analysis technique used was descriptive statistical analysis. The results showed that partially the variable price fluctuations had a positive and significant effect on the purchasing power of Muslim groceries traders with the result t count 6.111 > t table = 2.000, with a significance level of 0.000 <0.05. The magnitude of the effect of price fluctuations on the purchasing power of Muslim basic food traders is 32.4%, while the rest is influenced by other factors not included in this study.